(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The world and the business environment are constantly witnessing many economic changes that have led to the expansion of the business’ volume due to mergers and the increase in an investments volume and the complexity of business and the transformation of some systems, which was reflected on the size of the risk and uncertainty which led to necessity of a presence of transparent and objective accounting information In the way that reflects the financial performance of the economic units to be available to all users of that information, therefore, The need for the existence of indicators for transparency in the disclosure of accounting information that these units adhere to. Standards & Poor’s indicators, which included items for financial reporting, many of them are not reveal by the Iraqi commercial banks,The research sample in its annual reports, as it is committed to what is stipulated in the laws and instructions of the supervisory authorities and that many of Standards & Poor’s indicators are not stipulated by these laws, and the subject of audit disclosure according to Standards & Poor’s indicators is an important topic that has received attention in recent times, which called for the necessity of a program to audit accounting information according to Standards & Poor’s indicators for reasons including the lack of full disclosure And transparency in relation to the accounting information of many companies in the financial markets.